tan − 1 ( 4 3 ) − 2 tan − 1 ( 5 1 ) = cos − 1 ( d c )
The equation above holds true for coprime positive integers c and d . Find c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Instead of applying the sum/difference formula, it is often easier to manipulate the complex number interpretation. This approach can be easily generalized.
First, observe that:
( 5 + i ) 2 4 + 3 i = 2 4 + 1 0 i 4 + 3 i = ( 2 4 − 1 0 i ) ( 2 4 + 1 0 i ) ( 4 + 3 i ) ( 2 4 − 1 0 i ) = 2 4 2 + 1 0 2 1 2 6 + 3 2 i = 3 3 8 6 3 + 1 6 9 8 i
If we take the polar representation of this number, we get that:
[ 1 2 + 5 2 C I S ( tan − 1 5 1 ) ] 2 4 2 + 3 2 C I S ( tan − 1 4 3 ) = ( 3 3 8 6 3 ) 2 + ( 1 6 9 8 ) 2 C I S ⎝ ⎛ cos − 1 ( 3 3 8 6 3 ) 2 + ( 1 6 9 8 ) 2 3 3 8 6 3 ⎠ ⎞
Now, simplifying the calculations and considering the angle measure, we get that:
tan − 1 4 3 − 2 × tan − 1 5 1 = cos − 1 6 5 6 3
Problem Loading...
Note Loading...
Set Loading...
Let α = tan − 1 ( 4 3 ) , β = tan − 1 ( 5 1 ) and γ = cos − 1 ( d c ) . Therefore, we have:
α − 2 β ⟹ tan γ = γ = tan ( α − 2 β ) = 1 + tan α tan 2 β tan α − tan 2 β = 1 + 4 3 ⋅ 1 − 2 5 1 5 2 4 3 − 1 − 2 5 1 5 2 = 1 + 4 3 ⋅ 1 2 5 4 3 − 1 2 5 = 6 3 1 6
Now, we have:
d c = cos γ = sec γ 1 = sec 2 γ 1 = 1 + tan 2 γ 1 = 1 + ( 6 3 1 6 ) 2 1 = 6 5 6 3
⟹ c + d = 6 3 + 6 5 = 1 2 8